EFL STUDENTS’ MOTIVATION IN ENGLISH SPEAKING CLASS AT THE TWELFTH GRADE OF SENIOR HIGH SCHOOL DURING COVID-19 PANDEMIC - Rosma Nofi Damayanti; Putri Kamalia Hakim; Totoh Tauhidin Abas (PROJECT (Professional Journal of English Education), 2022)
Learning speaking skill is one of the important components for mastering English skills of EFL students, including Indonesian students. However, this learning process is not easy to do, because English in Indonesia as a foreign language and also difficult to do in the current COVID-19 pandemic situation. This has an effect on students' motivation in learning to speak English. Motivation has an important role in the success of learning speaking foreign languages including English. The purpose of this study is to analyze the motivation of EFL students in English speaking class  during COVID-19 pandemic based on Gardner's theory and to analyze the difficulties in speaking English that will affect students' motivation. This study was conducted at a senior high school in Bekasi, Indonesia. The participants consisted of eight students in twelfth grade. The research design in this study used a case study. Data was collected through observation, focus group discussion (FGD), and documentation. Observation and FGD was carried out via Zoom meeting. The data analysis used is thematic analysis. The result of this study is the students have instrumental and integrative motivation. However, students are motivated more instrumentally than integratively. The most students are instrumentally motivated for future interests such as as get a better job, continuing education, and to achieve success in the future. Then, many students experience difficulties in pronunciation and grammar which can influence their motivation in speaking English. This study has limitations, because the participants only consisted of eight students from twelfth grade. Keywords:  EFL Students, Motivation, Speaking